2020
DOI: 10.1002/ghg.2029
|View full text |Cite
|
Sign up to set email alerts
|

Fugitive methane gas migration around Alberta's petroleum wells

Abstract: Methane emission quantification from gas migration (GM) and surface casing vent flow (SCVF) is needed to support strategic methane reduction targets and mitigate explosion and groundwater quality risks. This paper assessed which of 451 990 Alberta oil and gas wells should have been (or will be) tested for SCVF and/or GM according to regulations, and compared the results with the provincial GM testing database. As of 2017, GM testing was required on 3.5%, and reported for 0.75%, of Alberta's energy wells. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 9 publications
0
27
1
Order By: Relevance
“…In addition to how well an abandoned well is plugged, leakage occurrence and rate depend on the integrity of the well (Gasda et al, 2004;King and King, 2013;King and Valencia, 2014;Davies et al, 2014;Lackey et al, 2017;Wisen et al, 2019;Ingraffea et al, 2020;Hammond et al, 2020;Abboud et al, 2020). Surface casing vent flows, surface casing pressures, and gas migration-all indicators of subsurface leakage-at active and unplugged abandoned wells-have been observed at 5.6% of wells in Pennsylvania (Ingraffea et al, 2020), 6.9% of wells in Colorado (Lackey et al, 2017), and 10.8% of wells in British Columbia (Wisen et al, 2019).…”
Section: Barriers and Limitations Of Well Pluggingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to how well an abandoned well is plugged, leakage occurrence and rate depend on the integrity of the well (Gasda et al, 2004;King and King, 2013;King and Valencia, 2014;Davies et al, 2014;Lackey et al, 2017;Wisen et al, 2019;Ingraffea et al, 2020;Hammond et al, 2020;Abboud et al, 2020). Surface casing vent flows, surface casing pressures, and gas migration-all indicators of subsurface leakage-at active and unplugged abandoned wells-have been observed at 5.6% of wells in Pennsylvania (Ingraffea et al, 2020), 6.9% of wells in Colorado (Lackey et al, 2017), and 10.8% of wells in British Columbia (Wisen et al, 2019).…”
Section: Barriers and Limitations Of Well Pluggingmentioning
confidence: 99%
“…However, identifying attributes linked to higher leakage frequencies has been found to be challenging due to incomplete databases (Montague et al, 2018). Moreover, subsurface gas migration pathways are "rarely clear," and "not all remedial operations will be completely successful" (Abboud et al, 2020).…”
Section: Barriers and Limitations Of Well Pluggingmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive reform, federal governments, inadequate enforcement, leakage testing, legal abandonment, management strategies, methane reduction targets, mitigation strategies, monitoring, policy initiatives, provincial requirements, regulations, state agencies, state regulators, state reporting, testing procedure. Bishop (2013), Ho et al (2016), Alboiu and Walker (2019), Kang et al (2019b) , (Kang et al 2021), Abboud et al (2020), Lavoie et al (2022) Measurements of CH4 emissions Leakage Broken well casing, casing leakage, cement failure, equipment leaks, ethane, fugitive emissions, gaseous emissions, geochemistry, geological formations, high emitters, leak points, leakage pathways, methane plumes, noble gas concentrations, point sources, preferential paths, production-normalized emissions, soil gas methane, surface casing vent flow, thermogenic gas, upstream oil and gas, volatile organic compounds, wellheads. Gasda et al (2004), Miller et al (2013), Davies et al (2014), Kang et al (2014), PĂ©tron et al (2014), Warneke et al (2014), Nathan et al (2015), Zavala-Araiza et al (2015), (Zavala-Araiza et al 2018), Allen (2016), Boothroyd et al (2016), Omara et al (2016), Townsend-Small et al (2016), Atherton et al (2017), Emran et al (2017), Johnson et al (2017), Lavoie et al (2017), Moortgat et al (2018), Pekney et al (2018), Cahill et al (2019), Fox et al (2019), Hoschouer and Townsend-Small (2018), Johnson et al (2019), Pandey et al (2019), Riddick et al (2019), …”
Section: Not Applicablementioning
confidence: 99%
“…Although there is much diversity in the abandonment protocols of the regulatory body across the globe, the goal of the process is to eliminate the potential risks to the environment [2], [6]. Recent studies, however, showed that abandoned wells are leaking Methane [7]- [9]. Improper placement of plugs may be considered as one of the possible reasons for such leaks.…”
Section: Introductionmentioning
confidence: 99%